Strategic bootstrapping - Rutherford, Matthew W. (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2015)
This book is about helping entrepreneurs sift through the "noise" regarding bootstrapping a start-up. Ultimately, the cold-hard facts on bootstrapping will be presented. Practically speaking, most entrepreneurs should avoid bootstrapping. However, realistically, most entrepreneurs will need to engage in some form of bootstrapping. The argument then, importantly, shifts to how should one bootstrap? In this era of lean start-ups, effectuation, and bricolage, bootstrapping is oft romanticized but seldom analyzed. This book is different from other bootstrapping books in two key ways. First, it draws on evidence from scientific study to offer best practices. Second, it utilizes this evidence to help entrepreneurs thrive-- not just survive.
1. Bootstrapping described -- 2. Bootstrapping and the problem of being new -- 3. New venture finance considerations for the bootstrapper -- 4. Financial bootstrapping -- 5. Bootstrap strategically -- 6. Typologies for strategic bootstrapping success -- References -- Index.
Includes bibliographical references (pages 75-83) and index.
Title from PDF title page (viewed on January 31, 2015).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: New business enterprises -- Finance; Bootstrapping; new venture strategy; new venture finance; Electronic books